Dispositional free riders do not free ride on punishment - Till O. Weber (Nature Portfolio, 2018)
Strong positive and strong negative reciprocators reward cooperation and punish defection, respectively, regardless of future benefits. Here, Weber and colleagues demonstrate that dispositions towards strong positive and strong negative reciprocity are not correlated within individuals.